Filsafat Islam; Sebuah Identifikasi Pandangan Hidup - Abdullah Muslich Rizal Maulana (Universitas Darussalam Gontor, 2017)
The topic of Islamic philosophy has always been attracted its reader to a wide yet specific subject including the identification of Islamic Philosophy which related to the relation between its origin and Worldview of Islam, the adaption of Greek philosophy into Islamic Philosophy, and the implications which emerged during and after the glory of Islamic Civilization. This paper will try to elaborate the term of “Islamic Philosophy” from its etymological meaning as well as the identification that taken from revelationbased worldview of Islam. As the beginning, the definitions of “philosophy” will be derived from number of authoritative scholars. The suitability between Islamic Worldview and the Islamization of Greek Philosophy will answer of the questions about ‘the originof Islamic Philosophy’; including the relation between both the important of revelation (wahy) and semantic interpretation. The discussion is continued widely as well on the history of translation in the time of the Caliph Ma’mun, Abbasid, when the civilization of Islam was in its golden era. Initiated by the caliph himself, this period has introduced many authoritative Muslim scholars in translation of knowledge scripts as well as described a lot of unique facts which rarely mentioned in the general literature such as how does the system of Bayt al-Hikmah work, interreligious relation between Scholars, and even the given salary for the Scholars. Lastly, this paper will redefine the historicity and ethnicity of philosopher explaining why does the reason of the term “Islamic Philosophy” become the most appropriate definition. In the deeper analysis, we do not only see ‘Islamic Philosophy’ as a claim of term but it is also as the ‘worldview identification’. Islamic philosophy, has indeed successfully assimilated the sophisticated assimilation of the thought of Greek Philosophy by all of its distinctive and characteristics.",